Genetic structure of common bottlenose dolphins (Tursiops truncatus) inhabiting adjacent South Florida estuaries – Biscayne Bay and Florida Bay - Litz, Jenny A.; Hughes, Colin R.; Garrison, Lance P.; Fieber , Lynne A.; Rosel , Patricia E. (J. Cetacean Res. Manage., 2023)
Coastal common bottlenose dolphins show a variety of migration and residency patterns adding to the difficulty of defining stocks for management purposes. Genetic structure plays an important role in identifying population stocks of dolphins. This study examines genetic differentiation in common bottlenose dolphins both between two social groups occurring in Biscayne Bay, Florida and between Biscayne Bay and an adjacent group of dolphins in Florida Bay. Skin biopsy samples were sequenced at the mitochondrial DNA (mtDNA) control region and genotyped at microsatellite loci. Significant genetic differentiation was found between bottlenose dolphins in Biscayne Bay and Florida Bay (mtDNA FST = 0.139, p ≤ 0.001; microsatellite FST = 0.042, p ≤ 0.001) supporting independent management stock status for these two populations. Within Biscayne Bay, evidence of weak but significant population differentiation was found between the two social groups using microsatellite markers (FST = 0.0149, p ≤ 0.009); however, differentiation was not evident from the mtDNA-based estimates of FST and φST. The lack of differentiation at mtDNA coupled with field observations indicating overlapping home ranges for these two groups suggests ongoing, though perhaps low, levels of interbreeding. These data are insufficient to warrant splitting the Biscayne Bay management stock at this time.